CULTURAL HERITAGE IN THE EFL CLASSROOM: A PATH TO SUSTAINABLE DEVELOPMENT - Alaeddine YOUCEFI, Asma DJAIDJA, Khawla MILIANI & Said ZIOUCHE (Ziglôbitha)
Abstract: This article reviews the crucial role of cultural heritage in fostering sustainable development, with a particular focus on the Algerian context. It investigates how cultural heritage, both tangible and intangible, serves not only as a source of national identity and collective memory but also as a dynamic resource for education, social cohesion, and economic development. This paper focuses on the relationship between culture and heritage, identifying various points of connection between UNESCO's conventions and the practice of cultural conservation in Algeria. It also examines the role of civil society organizations in heritage conservation and awareness-raising. A special emphasis is placed on integrating cultural heritage into English as a Foreign Language (EFL) teaching, positioning it as a pedagogical tool to enhance linguistic competence and intercultural understanding. By integrating heritage, education, and sustainability, the article recommends for a comprehensive strategy that aligns cultural preservation with contemporary developmental goals.